IMPROVING STUDENTS ACHIEVEMENT IN WRITING NARRATIVE TEXT BY APPLYING SPORE STRATEGY - Putri Febrini Sianturi; Amrin Saragih (Universitas Negeri Medan, 2014)
This study aims to discover the improvement of the students’ achievementin writing narrative text by applying Spore Strategy. The objective of this study isto find out whether the Spore strategy can improve students’ achievement inwriting narrative text or not. This study was conducted by using classroom actionresearch. The subject of the research was class XI IPA 2 of SMA Negeri 6 Medanwhich consists of 34 students. This study applied quantitative and qualitative data.The data of this study were obtained quantitatively through writing test whichshow that the students score kept improving in every test and qualitatively basedon diary notes, observation sheet and interview sheet which show that teachinglearning process ran well, the students were active, enthusiastic, and interested inwriting. In the first test, the mean score was 56.8. In the second test, the meanscore was 67.2, and in the third test the mean score was 81.2.The researchfindings indicated that Spore Strategy significantly improved students’achievement in writing narrative text.